Synthesis, characterization, and radioprotective activity of α, β-unsaturated aryl sulfone analogs and their Tempol conjugates12. Issue 5 (28th March 2017) - Zhou, Nan; Feng, Tian; Shen, Xin; Cui, Jiahui; Wu, Rangxin; Wang, Libin; Wang, Siwang; Zhang, Shengyong; Chen, Hui
Abstract : Some novel α, β-unsaturated aromatic sulfone analogs and Tempol conjugates are prepared and evaluated for their radioprotective activity, revealing that the agents have both prophylactic and mitigation effects against radiation damage. Abstract : Some novel α, β-unsaturated aromatic sulfone analogs (5a–5m ) and their Tempol conjugates (6a–6e ) have been synthetically prepared, characterized and evaluated for their radioprotective activity under γ-ray radiation. The Tempol conjugates were characterized by X-ray single crystal diffraction. In vitro studies showed that5a, 5b and6b had superior activities to Ex-Rad pre-treated before 5 Gy irradiation, and5a, 6a and6b had better activities than Ex-Rad after 5 Gy irradiation, while5a, 6a and6b exhibited both prophylactic and mitigation effects, indicating the advantage of combining α, β-unsaturated aromatic sulfones with Tempol nitroxide. Both p53 and phospho-p53 levels were significantly lower in compound-treated cells than those in untreated irradiated cells. The conjugates offer an improved radioprotective ability, which is an advantage in the treatment protocol.